Four new taxa of acaulescent Syagrus (Arecaceae) from Brazil - Noblick, Larry Ronald; Lorenzi, Harri; Souza, Vinicius C. (Phytotaxa, 2014)
Three new species and a new subspecies of acaulescent Syagrus palms are described as new to science. These occur in the central western cerrado region of Brazil: Syagrus emasensis and S. menzeliana from southwestern Goiás, S. guimaraesensis from south central Mato Grosso and finally S. graminifolia subsp. cabraliensis from north central Minas Gerais.